POLÍTICA DE COMUNICAÇÃO PARA INSTITUIÇÕES EDUCACIONAIS:O CASO DA REDE METODISTA DE EDUCAÇÃO - Silveira, Moisés Lemes da (2012)
The aim of this thesis was to first identify trends in communication processes and in organizational management institutional models existing in Methodist higher education institutions located in Brazil, seeking to find similarities and differences between communication processes arising from the implementation of the new structure adopted for the network management of the Methodist Education and its Shared Services Center. Then a Policy and Communication Guidelines model was proposed, bringing together the main activities related to the business communication processes that were identified during the preparation of this thesis. The methodology used was qualitative research, because it was the research method that best adapted to the proposed problem. To set the type of study, first there was an exploratory research through interviews with six managers of the referred network, and five managers who respond for the communication and marketing areas, using to this end, questionnaires containing both structured and unstructured questions. From the results obtained in the research, Human Resources, Information and Technology and Communication and Marketing department s activities were analyzed, to identify the contribution of each in the institutional communication processes consolidation. It was concluded that the model of policies and communication guidelines proposed in this paper, may allow both the Methodist Education Network and other higher education institutions to set the boundaries of their actions in objective procedures and criteria considered essential for enterprise management.